The Assessment of the Orthorexia Nervosa Tendencies among Postpartum Women. - Baser, Duygu Ayhan; Cankurtaran, Mustafa (Konuralp Medical Journal / Konuralp Tip Dergisi)
Objective: Orthorexia Nervosa is a new eating disorder and is known as an excessive control of quality of the eaten foods. During postpartum period, related to the physiological and medical changes, it was stated that most of the women have concerns about their body image and therefore they have tendency to change their lifestyle, and it can lead mothers to Orthorexia Nervosa. The aim of this study was to assess the Orthorexia Nervosa tendencies of postpartum women and investigate the related factors. Methods: This descriptive study was carried out among postpartum women between 1st December 2018-1st February 2019. We contacted with the women via e-mails through a social media group special for postpartum women which had 10.350 members at the time of study. The minimum sample size for universe was estimated as 370 women, assuming 95% confidence interval and 5% sampling error. The questionnaire consists of two parts: the general features of participants and the ORTO-11 questionnaire. Results: The mean ORTO-11 scale score of all participants (N=511) was 22.68±4.09 (min=12; max=35) and had statistically significant relationship with age, working status, vocation, family style, the understanding of being healthy, physical activity, diet status and the order of nutrition status. According to cut-off point, 87.7 % (n=426) of the participants were found to be at risk of developing Orthorexia Nervosa. Conclusions: The tendency toward Orthorexia Nervosa was greater among mothers in postpartum period. Also the mothers who change their eating habits and change the physical activity status after delivery had higher ON tendency than others. So the postpartum period is very important to follow up the mothers about ON and such eating disorders because of the changing lifestyle habits. Family physicians have a critical role in this regard with their preventive medicine qualifications.